Steel-Composite Armour Panels Against RPG with the Use of Nanostructured Bainite-Austenite Steel Plates - Wojciech BURIAN; Jarosław MARCISZ; Jerzy STĘPIEŃ; Lech STARCZEWSKI; Małgorzata WNUK (Problemy Mechatroniki)
Test results of perforation resistance of experimental steel-composite panels containing nanostructured bainite-austenite (NANOS-BA®) steel plates against RPG grenade are presented. Experimental panels were modified in the range of thickness of plates and grade of steel and in a type of composite materials. In firing tests with PG-7W and PG-7WM grenades, the high protection efficiency at about 20% reduction in areal density in comparison with panels used at present were achieved. On the basis of firing test results of steel plates used in experimental panels, proper level of toughness and strength at high resistance to piercing was selected. For the final design of experimental panels, different properties of steel plates for particular layers of the panel were proposed. Laminated materials of density in the range of 1.0÷2.1 g/cm3 were used for experimental steel composite panels.